2016
DOI: 10.1071/bt15143
|View full text |Cite
|
Sign up to set email alerts
|

An unspecific phytotoxin oxalic acid and its effect on sunflower proteome

Abstract: Oxalic acid (OA) is found naturally in many plants and animals: it plays diverse roles in nature. It is an important pathogenicity determinant of many necrotrophic pathogens including Sclerotinia sclerotiorum (Lib.) de Bary. In order to understand the resistance mechanisms in Helianthus annuus L., a proteomic study was conducted on sunflower 12 h after inoculation by OA. A total of 17 differentially expressed proteins (either OA-induced or -suppressed proteins) were identified as a result of OA treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Flavonols, such as quercetin have been reported to provide resistance to pathogen attack by suppressing ATPase activity of DNA gyrase (Babii et al, 2016;Naoumkina et al, 2010;Plaper et al, 2003). Similarly, kaempferide (flavonol triglycoside) produced by Dianthus caryophyllus is a fungitoxic compound against Fusarium oxysporum (Curir, Dolci, & Galeotti, 2005;Monazzah, Enferadi, Soleimani, & Rabiei, 2016). Flavonoids may be involved in the auxin transportation to the infected root by P. brassicae for gall formation (Paesold, Siegel, Seidel, & Ludwig-Müller, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonols, such as quercetin have been reported to provide resistance to pathogen attack by suppressing ATPase activity of DNA gyrase (Babii et al, 2016;Naoumkina et al, 2010;Plaper et al, 2003). Similarly, kaempferide (flavonol triglycoside) produced by Dianthus caryophyllus is a fungitoxic compound against Fusarium oxysporum (Curir, Dolci, & Galeotti, 2005;Monazzah, Enferadi, Soleimani, & Rabiei, 2016). Flavonoids may be involved in the auxin transportation to the infected root by P. brassicae for gall formation (Paesold, Siegel, Seidel, & Ludwig-Müller, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since OA can regulate antioxidant system in infected plants (Williams et al 2011), it is important to compare the antioxidant system of lines with different resistance levels to S. sclerotiorum infection in order to better understand the resistance mechanisms towards S. sclerotiorum in sunflower. The previous studies also indicated the increased activity of shikimate dehydrogenase (SKDH) and protein abundance of flavonol synthase in sunflower plants treated by OA which might implicate the induction of phenylpropanoid pathway (Tahmasebi-Enferadi et al 2011;Monazzah et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…So, the protein characterizations could lead to the discovery of new bioactive molecules hence increases the medicinal values of P. macrocarpa (Capriotti et al., 2013). It was also suggested that the different represented proteins in plants could generate knowledge about cell signaling pathways, providing supplementary informtion and also, it is essential in understanding the proteome changes of the plant in response to pathogens (Cipriano et al., 2015; Monazzah et al., 2016).…”
Section: Introductionmentioning
confidence: 99%